Dobras da pele: processo maiêutica e a presença do corpo do ator no teatro de animação contemporâneo - Andrade, Raquel Mützenberg (2017)
This work intends to discuss contemporary manifestations of the theater of animation, in which are registered several productions in which the actor offers movements, voice and breathing to a puppet or object, and also to parts of his own body to constitute structurally the object to be animated. In these manifestations appears poetics that are characterized by the creation of "folds" in the relation actor-puppet and in the function of the bodies of the actor and the puppet. The new relationships between the creative bloke and the created object, predominating the demystification in the animation of puppet, are understood as triggers of processes of singularization and, in this research, will be analyzed from the experience, from the feeling with the own skin. Based on the notion of Deleuze's folding and discussions about subjectivity, we will reflect on the creative process of the "Maiêutica" performance, created during this reasearch in a workshop with the puppeteer Natacha Belova, and performed with a puppet that unfolds from the body of the actor-animator.